Effects of Low pH on Photosynthesis, Related Physiological Parameters, and Nutrient Profiles of Citrus - Long, An; Zhang, Jiang; Yang, Lin-Tong; Ye, Xin; Lai, Ning-Wei; Tan, Ling-Ling; Lin, Dan; Chen, Li-Song (Frontiers in Plant Science, 2017)
Seedlings of 'Xuegan' (Citrus sinensis) and 'Sour pummelo' (Citrus grandis) were irrigated daily with nutrient solution at a pH of 2.5, 3, 4, 5 or 6 for nine months. Thereafter, seedling growth, root, stem and leaf concentrations of nutrient elements, leaf gas exchange, pigment concentration, ribulose-1,5-bisphosphate carbohylase/oxygenase activity and chlorophyll a fluorescence, and root and leaf relative water content, total soluble protein level, H2O2 production and electrolyte leakage were investigated in order to (a) determine how low pH affects photosynthesis, related physiological parameters and mineral nutrient profiles; and (b) to understand the mechanisms by which low pH causes a decrease in leaf CO2 assimilation. pH 2.5 greatly inhibited seedling growth and many physiological parameters were altered only at pH 2.5; pH 3 slightly inhibited seedling growth; pH 4 had almost no influence on seedling growth; and seedling growth and many physiological parameters reached a maximum at pH 5. No seedlings were killed at each given pH. These results demonstrated that citrus were insensitive to low pH. H+-toxicity might directly damage citrus roots, hence affecting the uptake of mineral nutrients and water. H+-toxicity, decreased uptake of nutrients (i.e., nitrogen, phosphorus, potassium, calcium and magnesium) and water were probably responsible for the low pH-induced inhibition of growth. Leaf CO2 assimilation was inhibited only at pH 2.5. The combinations of impaired photosynthetic electron transport chain, increased production of reactive oxygen species, and decreased uptake of nutrients and water might account for the pH 2.5-induced decrease in CO2 assimilation. Mottled bleached leaves only occurred in pH 2.5-treated C. grandis seedlings. Furthermore, the pH 2.5-induced alterations of leaf CO2 assimilation, water use efficiency, chlorophylls, polyphasic chlorophyll a fluorescence (OJIP) transients and many fluorescence parameters, root and leaf total soluble proteins, H2O2 production and electrolyte leakage were slightly greater in C. grandis seedlings than in C. sinensis ones. Obviously, C. sinensis was slightly more tolerant to low pH than C. grandis. In conclusion, our findings provided some novel clues on the causes of low pH-induced inhibition of seedling growth and leaf CO2 assimilation.